How pseudo is an inflammatory pseudotumor? - Gude, Dilip; Rayudu, Ramasubba; Bansal, Dharam (Indian Journal of Medical and Paediatric Oncology, 2011)
Inflammatory pseudotumor (IPT) is a rare lesion of unclear etiology reported in various organs. Although mostly benign, these tumors may pose a therapeutic challenge in cases of recurrence. We report the case of a young male who presented with a clinical and radiological picture suggestive of a malignancy in the thorax and upon evaluation was noted to have IPT of the lung. Complete surgical resection was done with no evidence of tumor recurrence. We review the literature and discern the epidemiological, clinical, pathophysiological and management aspects of IPTs.
Keywords: Inflammatory pseudotumor; lung; malignancy; recurrence